Nilai-Nilai Cinta Kasih dalam Film Layar Lebar Rindu Kami PadaMu - Anggitya, Paramastu Titis (JURNAL KOMUNITAS, 2015)
By nature, every human being endowed the feelings of love in different levels, that affects behavior and view of love values differences. The fading of love in human beings today encourages various efforts to place love compassions in human life. Through a film titled ‘Rindu Kami PadaMu’, longing of love shown by using certain symbols which is not easily understood by the audience at a glance as efforts to place love compassions. This study is result of a qualitative research using Roland Barthes semiotic analysis approach and Robert Sternberg’s typology of love theory. The result showed that ‘Rindu Kami PadaMu’ is a film that reflects the longing of love, including love for family, spouse, human beings, God and the environment. This film teaches the importance of love values placement in universal life. Based on Robert Sternberg’s typology of love theory, it can be seen that the types of love in this film consist of nonlove, liking, romantic love, fatuous love, and consummate love which are variously experienced by all characters.